2020
DOI: 10.1001/jamapediatrics.2020.0382
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sexual Health Interventions With Sexual Health Outcomes in Black Adolescents

Abstract: IMPORTANCEBlack adolescents are at increased risk of contracting HIV and other sexually transmitted infections (STIs) and experiencing unplanned pregnancy. Although sexual health interventions aimed at decreasing these risks exist, evidence of the association between sexual health interventions and the sexual behavior of black adolescents has not been synthesized to our knowledge. OBJECTIVE To examine the associations between sexual health interventions and behavioral, biological, and psychological outcomes.DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 85 publications
1
38
0
4
Order By: Relevance
“…As is evidenced by our key words, we initially planned to do one metaanalysis on interventions for Latinx and black adolescents but ultimately determined it would produce more meaningful results to understand each population separately. 43 Other studies were located by examining previous reviews and metaanalyses 18,[28][29][30][31][32][44][45][46] and examining the reference lists of all included articles. This initial search produced 3068 different articles.…”
Section: Search Strategymentioning
confidence: 99%
“…As is evidenced by our key words, we initially planned to do one metaanalysis on interventions for Latinx and black adolescents but ultimately determined it would produce more meaningful results to understand each population separately. 43 Other studies were located by examining previous reviews and metaanalyses 18,[28][29][30][31][32][44][45][46] and examining the reference lists of all included articles. This initial search produced 3068 different articles.…”
Section: Search Strategymentioning
confidence: 99%
“…Although TINAD was a brief intervention that could be delivered in just a single classroom session, preliminary results from this study are in line with others that suggest even brief programming can impact adolescent health cognitions and behavior [30], and some meta-analyses that show Table 3 Changes from pretest to posttest in prescription opioid misuse knowledge, attitudes, self-efficacy, and intentions The same pattern of results emerged when analyses were run separately among adolescents who reported previous opioid misuse and among adolescents who did not report previous misuse. Knowledge: n = 484; Attitudes: n = 537; Self-efficacy: n = 519; Intentions: n = 555 that health interventions for youth can be effective regardless of their duration [31][32][33]. Since TINAD is wide reaching, acceptable, and shows preliminary efficacy at promoting healthier cognitions regarding opioid misuse, as demonstrated by this study with middle school students and one other study with high school students [12], it seems fruitful to build on and improve the TINAD program so that in the future, we can expect adapted iterations to change adolescent opioid misuse intentions and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…There remain several groups of young people that experience additional vulnerabilities that place them at higher risk of poor sexual health, and it is likely that these individuals require a tailored approach that targets their specific needs. One such example is that of black American adolescents, with a recent meta-analysis finding that such sexual health interventions targeting this population successfully improved sexual health knowledge, attitudes and behaviour [14]. The authors concluded that there is a need for wide-scale dissemination of these programs to address racial disparities in sexual health across the US.…”
Section: Introductionmentioning
confidence: 99%